The Development of Photovoltaics in the Countries of Central and Eastern Europe in the Context of Regulatory Changes: A Case Study of the Czech Republic and Poland - Maciej Dzikuć; Arkadiusz Piwowar; Maria Dzikuć (Energies)
The Czech Republic and Poland are struggling with problems related to the development of photovoltaics. Both analyzed countries had periods of dynamic development of this renewable energy source (RES). However, neither the Czech Republic nor Poland have developed mechanisms that would lead to the stable development of photovoltaic installations in the long term. The analyses presented in this article demonstrate the implementation of extreme solutions by these countries, which led either to stagnation in the development of photovoltaics or to an excessive increase in the installed capacity, including RES, which then had to be stopped due to, for example, the failure of the power grids to match the increasing capacity. This article conducted research based on secondary data and using the Foresight method. The aim of this manuscript is to present the conditions related to the development of photovoltaics in the Czech Republic and Poland. This article also points to the barriers limiting the development of this type of RES and the potential of solutions related to, e.g., energy storage, which will allow for maintaining stable development of photovoltaics in the future and will prevent excessive overloading of power grids. The research results indicate that in the context of further development of photovoltaics in the study area, what is important are, e.g., changes in legal regulations and financial incentives that will enable the development of micro-installations within energy communities to a greater extent, including co-financing for energy storage. Other factors were also noted, including interconnection capacity within the energy systems of these countries, as well as externally.